2004
DOI: 10.1117/1.1646413
|View full text |Cite
|
Sign up to set email alerts
|

Pump-probe detection of laser-induced microbubble formation in retinal pigment epithelium cells

Abstract: Microsecond laser pulses are currently being investigated in a new ophthalmic procedure for treatment of disorders associated with the retinal pigment epithelium (RPE). The precise mechanism for microsecond laser-induced RPE damage, however, has not been determined. We have previously shown that short pulse laser irradiation in the nanosecond to picosecond time domain causes transient microbubble formation around melanin granules in pigmented cells. Nanosecond time-resolved microscopy was previously used to vi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
32
1

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1
1

Relationship

1
8

Authors

Journals

citations
Cited by 51 publications
(37 citation statements)
references
References 13 publications
4
32
1
Order By: Relevance
“…30 Previous studies have suggested that the transition from cavitation-induced to thermal damage is expected to take place somewhere within the microsecond regime. 31,32 It was shown that RPE cell death coincides with bubble formation for 3-, 5-, and 6-s pulses, 31,32 while RPE cells were damaged without cavitation formation for 50-s pulses. 32 However, these reports did not examine pulse durations between 5 and 50 s, a critical parameter range for scanning selective targeting of the RPE.…”
Section: Introductionmentioning
confidence: 97%
“…30 Previous studies have suggested that the transition from cavitation-induced to thermal damage is expected to take place somewhere within the microsecond regime. 31,32 It was shown that RPE cell death coincides with bubble formation for 3-, 5-, and 6-s pulses, 31,32 while RPE cells were damaged without cavitation formation for 50-s pulses. 32 However, these reports did not examine pulse durations between 5 and 50 s, a critical parameter range for scanning selective targeting of the RPE.…”
Section: Introductionmentioning
confidence: 97%
“…7,11,25 Studies have also shown that the microcavitation thresholds decrease with increasing number of pulses. 26 The RPE is believed to be the site for threshold damage for all nanosecond and picosecond laser exposures in the visible and NIR. In the NIR wavelength region, the ocular media and anterior structures of the eye (cornea and lens) begin to strongly absorb, but still transmit adequate energy to pose a risk to the retina.…”
Section: Mechanisms Of Short-pulsed Laser-inducedmentioning
confidence: 99%
“…Light melanosomes are predominately spherical, while the heavy melanosomes are predominately elliptical in shape, resulting in slight size differences between the two fractions. 26,29 However, no high-resolution imaging was used, and therefore, no precise knowledge of shape variance within each fraction was obtained. The melanosome fractions were separated in order to determine if differences in microcavitation threshold values occur.…”
Section: Melanosome Preparationmentioning
confidence: 99%
“…At subnanosecond exposures, other nonlinear damage mechanisms appear, such as shock-waves and laser-induced breakdown. (9) Multispot laser is also less painful for the patient, as thermal diffusion in the choroid, where pain receptors reside, has been reduced. Multispot laser allows spots to be delivered almost simultaneously and with greater regularity than conventional treatment.…”
mentioning
confidence: 99%